Clinical Trial of the Outpatient Management of Pyelonephritis in Pregnancy. Issue 2 (1995) - Brooks, Allyson M.; Garite, Thomas J.
Abstract : Objective: This study was designed to determine whether outpatient treatment of pyelonephritis in pregnancy can reduce costs without compromising safety or efficacy. Methods: Pregnant patients with uncomplicated initial episodes of acute pyelonephritis were considered for outpatient management. The outpatient treatment consisted of an initial dose of IV ceftriaxone (2 g), followed by daily outpatient IM ceftriaxone (2 g) until resolution of fever and flank tenderness, followed by a 10-day course of oral antibiotics. The study group was compared with a group requiring inpatient treatment and a historical control group meeting the criteria for outpatient management but having been treated as inpatients in the previous year. Results: Of the 34 treated as outpatients, only 4 (12%) required hospital admission and 1 developed an upper urinary tract recurrence. None of these patients had premature delivery or any other serious complication. The historical control group (N = 29) included 1 upper urinary tract recurrence, no preterm deliveries, and 1 case of acute respiratory disease syndrome. The outpatient group required an average of 3.4 daily outpatient visits compared with 3.9 days of hospitalization for the historical control group. The inpatient group (N = 39) was significantly more likely to require hospitalization >6 days ( P = 0.0004), with a trend toward more frequent upper urinary tract recurrences (6/39 vs. 1/34, P = 0.08). The cost analysis revealed a 3-fold difference between outpatient and inpatient therapy ($1, 100 vs. $3, 350, P < 0.001). Conclusions: The outpatient treatment of selected patients with pyelonephritis in pregnancy as a promising approach to reducing costs warrants further investigation.